Lithostratigraphy of Tabul Formation and Onshore Geology of Nunukan Island, North Kalimantan - Salahuddin Husein (Geological Engineering Department Universitas Gadjah Mada, 2017)
Nunukan Island is located in Northeast Kalimantan Basin, one of proliﬁc basin in western Indonesia. However, this island lies in northern verge of the basin and hydrocarbon exploration were limited before the 1940s. No detail geological ﬁeldworks has been published. This paper attempts to share geological information obtained from few accessible outcrops, particularly from the western part of the island where previous oil drilling were carried out. Most of the island have been built by Tabul Formation, which was also the main objective of reservoir for hydrocarbon exploration. It is composed of claystones, siltstones, and sandstones interbeds, deposited in transitional environment during Late Miocene. They exhibit coarsening upward sequence, the lower part composed of heterolitic sandstones deposited in tidal ﬂats, and the upper part composed of arkosic sandstones deposited in distributary channels and mouthbars. The eastern coastal strip was constructed by Tarakan conglomerates, which have been deposited in ﬂuvio-deltaic environment in Pliocene, unconformably over the Tabul clastics. Those Neogene deposition of paleo-Simengaris Delta apparently deformed and inverted in Plio-Pleistocene, contemporaneously with basaltic volcanism which spread widely over northeastern Borneo, which also observed in the northern half of the Nunukan Island